Bifidobacterium animalis subsp. lactis TG11 ameliorates loperamide-induced constipation in mice by modulating gut microbiota - Ma, Weiwei; Zhao, Yiyang; Liu, Yuyang; Wang, Yanyan; Yu, Shuang; Huang, Lili (Frontiers in Microbiology, 2025)
IntroductionConstipation is a common gastrointestinal disorder that can affect quality of life. Probiotics have garnered substantial attention for their potential to alleviate constipation. This study investigates the preventive effects of Bifidobacterium animalis subsp. lactis TG11 on loperamide-induced constipation in mice.MethodsMice were randomly assigned to normal control (NC), constipation model (CM), and low, medium, and high-dose TG11 treatment groups (LG, MG, HG). From days 1–14, LG, MG, and HG groups received 106, 107, and 108 CFU/mouse of TG11, respectively, while NC and CM groups received saline. On day 14, all groups except NC were administered loperamide (4 mg/kg) orally to induce constipation. Fecal samples were collected for short-chain fatty acid and gut microbiota analyses. Following a 16-hour fasting period, various parameters were assessed on day 15, including intestinal motility, fecal water content, defecation status, gut peptide levels in blood, and mRNA expression levels of SCF and c-kit in colonic tissue.ResultsTG11 significantly enhanced intestinal motility and maintained fecal water content. It normalized blood levels of MTL, SP, SS, ET-1, Gas, and VIP in constipated mice, promoted short-chain fatty acid production, and improved microbial metabolism. TG11 markedly upregulated mRNA expression of SCF and c-kit in colonic tissue. Metagenomic sequencing revealed that TG11 modulated gut microbiota composition, increasing the abundance of beneficial bacteria, particularly Muribaculum_sp. and uncultured_Duncaniella.DiscussionBifidobacterium animalis subsp. lactis TG11 demonstrates efficacy in ameliorating constipation, potentially through modulation of the gut microbiota composition.